STUDI EKSPERIMENTAL PENGENDALIAN LAJU KOROSI FATIK PADA ALUMINIUM 2024-T3 DI LINGKUNGAN AIR LAUT MELALUI PENAMBAHAN INHIBITOR KALIUM KROMAT (K2CrO4) - Waris Wibowo (UNIMAR AMNI Semarang, 2017)
Aluminum alloy 2024-T3 is widely used in manufacturing industries such as aircraft, automotive and ship industries due to its character as a good mechanical property. Aluminum alloy2024-T3, however, is easily suffered from corrosion attack when it is applied in corrosive environment such as sea water. One of the corrosion rate control methods is by applying inhibitor addition. This research aims to study the effect of K2CrO4 inhibitor in controlling the rate of corrosion of Al 2024-T3 in sea water. In this research, K2CrO4 was added to sea water environment with various concentrations of 0.1 %, 0.3% and 0.5%. Subsequently the corrosion rates were measured using a-three-electrode potential technique with saturated calomel (Hg2Cl2) as a referenced electrode whereas the auxiliary electrode was platinum (PT). Fatigue corrosion experiments was done using servo hydraulic testing engine, sinusoidal load was chosen with the stress ratio of R= Smin/Smaks = 0,1, and the frequence of 15 Hz, the voltage level used was 20%. Composition analyses, micro structure examination with Scanning Electron Microscope (SEM) were also done to get the supporting data. The results show that fatigue corrosion rate of aluminum alloy 2024-T3 with the additions of K2CrO4 inhibitor in the sea water tends to reduce at the optimum concentration of 0.5% of K2CrO4. It is indicated by the reduction of fatigue corrosion rate as amount of 32.13%. This inhibitor may hamper the rate of fatigue corrosion by oxidation so that it produces a compound (passive film) which covers the surface of Aluminum alloy 2024-T3 which is in turn it will reduce the attack of corrosion.Keywords : Aluminum Alloy 2024-T3, Fatigue Corrosion, K2CrO4 Inhibitor ABSTRAK Aluminium paduan seri 2024-T3 telah banyak diaplikasikan pada industri pesawat terbang, otomotif, dan kapal laut karena memiliki sifat mekanik yang baik. Namun demikian aluminium paduan 2024- T3 rentan terhadap korosi bila diaplikasikan di lingkungan yang korosif seperti air laut. Salah satu upaya untuk mengendalikan laju korosi adalah dengan penambahan inhibitor. Penelitian ini bertujuan untuk mempelajari pengaruh inhibitor kalium kromat (K2CrO4) dalam mengendalikan laju korosi Al 2024-T3 di lingkungan air laut. Pada penelitian ini, jenis inhibitor yang dipakai adalah kalium kromat (K2CrO4) yang ditambahkan di media air laut dengan variasi konsentrasi 0,1%; 0,3%; dan 0,5%. Selanjutnya laju korosi diukur dengan menggunakan metode sel potensial tiga elektroda yang menggunakan kalomel jenuh (Hg2Cl2) sebagai elektroda baku sedangkan elektroda tambahan digunakan platina. Pengujian korosi fatik dengan mesin uji servohidraulik, beban sinusoidal dipilih rasio tegangan R= Smin/Smaks = 0,1 dan frekuensi 15 Hz, level tegangan yang digunakan adalah 20%. Sebagai data pendukung dilakukan uji komposisi dan uji struktur mikro dengan Scanning Electron Microscope (SEM). Hasil penelitian ini memperlihatkan bahwa laju korosi fatik Al 2024-T3 dengan penambahan inhibitor kalium kromat (K2CrO4) di media air laut cenderung menurun pada konsentrasi optimum 0,5% K2CrO4, ditandai dengan penurunan laju korosi fatik sebesar 32,13%. Inhibitor ini dapat menghambat laju korosi fatik dengan cara mengoksidasi sehingga menghasilkan produk senyawa (lapisan pasif) yang dapat menutup permukaan Al 2024-T3 yang dapat mengurangi serangan korosi.Kata kunci : Aluminium Paduan 2024-T3, Korosi Fatik , Inhibitor K2CrO4